МУСТАҚИЛЛИК ЙИЛЛАРИДА ҚОРАҚАЛПОҒИСТОН ҲАЙВОНОТ ДУНЁСИНИ АСРАШГА ҚАРАТИЛГАН ТАДҚИҚОТЛАР ТАРИХИ - Хужаниязов, У. (SCIENCE and SOCIETY, 2016)
The article deals with the review of scientific research works of the scientists of Karakalpakstan in zoology in the historical-geographucal aspect for the years of Independence. The latest research works in trilogy, herpethology, ichtiology and ornithology are of a great importanse. There is a commentary to the research works devoted to the flora of the Aral seaside. The author emphasizes the particular care of the state and government about these investigations.